Impact of a Wastewater Treatment Plant Upgrade on Amphipods and Other Macroinvertebrates: Individual and Community Responses - Peschke, Katharina; Capowiez, Yvan; Köhler, Heinz-R.; Wurm, Karl; Triebskorn, Rita (Frontiers in Environmental Science, 2019)
In the present study we investigated the efficiency of additional wastewater treatment based on powdered activated carbon and its benefit for the ecosystem of a connected river system in the catchment area of Lake Constance, Southern Germany. We focused on the overall health status of gammarids and the integrity of the macrozoobenthic community. Samples were taken up- and downstream of a wastewater treatment plant (WWTP), as well as before and after its upgrading. The investigations showed that both sex ratio and fecundity of gammarids, as well as the macrozoobenthic community were affected by the effluent prior to the WWTP upgrade. After the upgrade, gammarids from the downstream site did not differ any longer from those collected upstream of the WWTP with respect to the investigated health parameters. Furthermore, the overall number of taxa and, particularly, the number of sensitive taxa within the macrozoobenthic community downstream of the WWTP increased considerably. Therefore, we conclude that the additional treatment with powdered activated carbon was highly efficient to improve invertebrate health and community integrity.